2016
DOI: 10.1095/biolreprod.116.140632
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bovine Sperm Interaction with Epithelium Differ Between Oviductal Isthmus and Ampulla

Abstract: In mammals, many sperm that reach the oviduct are held in a reservoir by binding to epithelium. To leave the reservoir, sperm detach from the epithelium; however, they may bind and detach again as they ascend into the ampulla toward oocytes. In order to elucidate the nature of binding interactions along the oviduct, we compared the effects of bursts of strong fluid flow (as would be caused by oviductal contractions), heparin, and hyperactivation on detachment of bovine sperm bound in vitro to epithelium on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 33 publications
3
51
1
1
Order By: Relevance
“…Our results showed that both heparin-pretreated and nonpretreated sperm rapidly attached to the epithelium of the preovulatory ampulla explants, as similarly observed in explants containing only ampullary epithelium (i.e., epithelium lacking underlying connective tissue of the lamina propria; Lefebvre & Suarez, 1996) and in confluent monolayers of the ampullary epithelium (Gualtieri & Talevi, 2000). In our current and previous experiments using explants (Ardon et al, 2016;Lefebvre & Suarez, 1996), it was clear that sperm bind primarily to the beating cilia of the explants and remain bound, despite rapid beating of both the cilia and the sperm flagella.…”
Section: Upregulated Tlr2 Protein Was Mainly Localized To Epitheliusupporting
confidence: 85%
“…Our results showed that both heparin-pretreated and nonpretreated sperm rapidly attached to the epithelium of the preovulatory ampulla explants, as similarly observed in explants containing only ampullary epithelium (i.e., epithelium lacking underlying connective tissue of the lamina propria; Lefebvre & Suarez, 1996) and in confluent monolayers of the ampullary epithelium (Gualtieri & Talevi, 2000). In our current and previous experiments using explants (Ardon et al, 2016;Lefebvre & Suarez, 1996), it was clear that sperm bind primarily to the beating cilia of the explants and remain bound, despite rapid beating of both the cilia and the sperm flagella.…”
Section: Upregulated Tlr2 Protein Was Mainly Localized To Epitheliusupporting
confidence: 85%
“…During maturation in the female reproductive tract, human sperm are exposed to elevated temperature, especially before and during ovulation, which is correlated with an increase in basal body temperature by 1°C. As spermatozoa are able to survive in the female reproductive tract for several days by binding to the ciliated epithelia of the fallopian tubes, they must eventually undergo hyperactivation to detach ( Ardon et al, 2016 ). Accordingly, CatSper-deficient spermatozoa that cannot hyperactivate are not able to ascend the fallopian tubes ( Ho et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results support a direct action of P4 on spermatozoa or simultaneously on both sperm and oviduct epithelial cell surface to trigger sperm release. It is likely that hyperactivation plays an important role in the release of spermatozoa from the oviduct epithelium in mammals (Demott & Suarez 1992, Chang & Suarez 2012, Ardon et al 2016. Spermatozoa with hyperactivated motility were observed while they detached from bovine mucosal folds of oviduct epithelium in vitro (Ardon et al 2016) and from the epithelium in entire oviducts retrieved from mouse females just after mating (Demott & Suarez 1992, Chang & Suarez 2012.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that hyperactivation plays an important role in the release of spermatozoa from the oviduct epithelium in mammals (Demott & Suarez 1992, Chang & Suarez 2012, Ardon et al 2016. Spermatozoa with hyperactivated motility were observed while they detached from bovine mucosal folds of oviduct epithelium in vitro (Ardon et al 2016) and from the epithelium in entire oviducts retrieved from mouse females just after mating (Demott & Suarez 1992, Chang & Suarez 2012. Hyperactivated spermatozoa display asymmetrical, high-amplitude flagellar movements (Yanagimachi 1970) that are not only important for sperm release but also essential for the penetration of the cumulus oophorus and the zona pellucida surrounding the oocyte (Hung & Suarez 2010).…”
Section: Discussionmentioning
confidence: 99%